Employment outcomes of ethnic minorities in Spain: towards increasing economic incorporation among immigrants and the second generation? - Fernández-Reino, M; Radl, J; Ramos, M (Cogitatio, 2018)
This article examines the labour market outcomes of immigrants in Spain, a country that has become a migration destination only since the end of the 1990s. Differentiating between first and second generation of immigrant descent, we compare the labour market involvement of the main ethnic groups with the majority group. One particular focus is to understand which minorities have been hit the hardest by the Great Recession. To this end, we use data from the European Union Labour Force Survey for the years 2008 and 2014, and more specifically the two ad-hoc modules on the labour market situation of migrants. Analysing men and women separately, we run a set of multivariate logistic regression models to control for compositional differences. In this way, we examine ethnic gaps not only in labour force participation but also in the degree of underutilisation of human capital, measured as workers’ level of over-education as well as the incidence of involuntary part-time employment. Our results show that while most origin groups do not show significantly lower employment participation than the majority group, the employment quality of immigrants in terms of involuntary part-time work and over-education is substantially worse, especially since the crisis.